Health Promotion and Disease Prevention Practices of the Teachers: Basis for Enhanced Wellness Program - Markhipolito P. Galingana; Angelito E. Alvarado; Ryan Mark R. Mallillin; Christel V. Mrcelo; Judiann L. Midang; Sharina S. Obien; Daniel N. Ortiz (Health Notions, 2022)
In the sedentary nature of an employee's most working status, this group can be at risk of developing non-communicable diseases and become susceptible to the Covid-19 pandemic. This study utilized a quantitative descriptive design for it aims to identify the practices of the respondents regarding health promotion and disease prevention that can serve as a basis for enhancement programs that may improve their health. The study’s respondents were the teachers of the educational institution, where they were selected using the purposive random sampling (fish bowl method) technique. Using the weighted mean, frequency and percentage, T-test and analysis of variance (ANOVA) as statistical treatment, the study's findings revealed that the majority of the respondents do not practice disease prevention. 71.7% don’t practice an annual checkup, 67.9% in blood pressure monitoring, 81.1% in weight monitoring, 96.2% in sugar level monitoring, 83% don’t take maintenance drugs, and 58.5% have an average sleep of 5-7 hours. While 81.1% are taking a vitamin supplement. In health promotion, the practices that are routinely done, together with the average mean are spiritual growth (2.99), interpersonal relationships (2.80) and stress management (2.50). While nutrition management (2.45), health responsibility (2.30) and physical activity (2.10) are only practiced sometimes. The study concluded that health teaching and programs are needed to improve the practices of the teachers in educational institutions regarding health promotion and disease prevention.Keywords: teachers; health promotion; disease prevention; health; practice